Finite element analysis of proximal femur using Charnley elite type stem / Muhamad Zaidi Salem. - Salem, Muhamad Zaidi (2009)
A total hip replacement (THR) is also called a hip arthroplasty. This is a surgical procedure that re-forms the hip joint.The objective of this study is to analyze the stress distribution of the femur with cemented Charnley Hip Prosthesis THR and finally compared to clinical result of patient that used this type of stem. Finite element method is used to study the biomechanical behavior of the intact and THR femur. This study is focused on the static analysis on maximum loading during standing, walking and upstairs. Femur and contact femur was drafted and imported from CATIA software to ANSYS. The femur has modulus elasticity and Poisson's ratio of 17 GPa and 0.33 respectively. The Charnley Elite stem is used a bio compatibility material that is stainless steel alloy (316 L). This type of material has modulus elasticity and Poisson's ratio of 193 GPa and 0.27 respectively. As a result, stairs climbing given a highest stress distribution in any of three components either contact femur, stem and cement. This analysis then compared to the clinical outcome and we can see that there have close relations about them. Failure of THR like aseptic loosening, osteolysis, migration, cement mantle thickness and prosthesis fracture are much related to this analysis.